2020
DOI: 10.1111/1365-2656.13279
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term change in water availability influences thermoregulation behaviours in a dry‐skinned ectotherm

Abstract: Mechanistic models of terrestrial ectotherms predict that climate warming will induce activity restriction due to heat stress and loss of shade, leading to the extinction of numerous populations. Such models rely on the assumption that activity patterns are dictated by simple temperature thresholds independent of changes in water availability. However, changes in water availability may further influence thermoregulation behaviour of ectotherms through dehydration risk perception, changes in water balance or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Since lizards of the genus Podarcis are species with a more sit-and-wait foraging mode, they might have less opportunities to adjust their behavioral activity and their "only" behavioral solution is therefore to lower importantly their body temperature in the absence of water. Unfortunately, we did not record movement activity in this study but previous investigations with lizards have shown that dehydration can reduce locomotor activity [29,43]. These hypotheses will have to be tested by studying a greater number of contrasting species with distinct foraging styles in the future and recording both body temperature and movement activity.…”
Section: Plos Onementioning
confidence: 96%
“…Since lizards of the genus Podarcis are species with a more sit-and-wait foraging mode, they might have less opportunities to adjust their behavioral activity and their "only" behavioral solution is therefore to lower importantly their body temperature in the absence of water. Unfortunately, we did not record movement activity in this study but previous investigations with lizards have shown that dehydration can reduce locomotor activity [29,43]. These hypotheses will have to be tested by studying a greater number of contrasting species with distinct foraging styles in the future and recording both body temperature and movement activity.…”
Section: Plos Onementioning
confidence: 96%
“…Climate is a powerful environmental factor driving the process of niche diversification in reptiles [1,2]. Tolerance to maximum temperatures in reptiles is evolutionarily constrained, possibly because of the importance of external heat sources in maintaining activity and for bodily water balance [3,4]. For these reasons, there is a significant association between the composition of reptile assemblages and thermal latitudinal gradients [5].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of most ectotherms improves smoothly with increasing body temperature until reaching an optima, and thereafter it drastically decreases ( Huey and Stevenson 1979 ). Zootoca vivipara ’s preferred body temperature in May/June, that is, during reproduction, is between 30 °C and 34 °C in males and around 29.5 °C in gravid females, and the range over which its performance is at least 80% of maximal performance is quite narrow ±2–5 °C ( Van Damme et al 1991 ; Gvoždík and Castilla 2001 ; Rozen-Rechels et al 2020 ). Its critical thermal maxima is between 43.8 °C and 44.1 °C.…”
mentioning
confidence: 99%
“…At this temperature its righting reflex is lost, leg spasms happen, and lethal or near lethal injury occurs ( Gvoždík and Castilla 2001 ; Leon and Bouchama 2015 ). Operative temperatures, that is, the body temperature of a perfectly thermoconforming animal ( Dzialowski 2005 ), reach more than 50 °C in the early afternoon at the beginning of May and on most study days, they were much above Z. vivipara ’s preferred body temperature (measured in May 2018, Rozen-Rechels et al 2020 ). However, in May, the daily maximal temperatures are much below the daily maxima occurring in summer (e.g., in May they were −7.2 °C lower than in summer 2018 in Nemours les Saint-Pierre, France, where Rozen-Rechels et al [2020] recorded operative temperatures [click on this weblink to see the daily maximal temperatures at Nemours les Saint-Pierre] ).…”
mentioning
confidence: 99%
See 1 more Smart Citation